Biodiesel from Crude Palm Oil: A Sustainable Development Strategy for Energy Security - Fakai, Usman Rufai; Ibrahim, Aliyu Kangiwa; Utono, Adamu Zubairu (International Journal of Applied and Scientific Research, 2024)
The study investigates the synthesis process, catalyst preparation, and implications of CPO biodiesel production, focusing on energy security, environmental sustainability, and greenhouse gas emissions reduction. The study uses eggshell-derived calcium oxide (CaO) catalysts for catalyst preparation, demonstrating a novel approach to catalyst synthesis. Results show consistent biodiesel yields of 78.6%, demonstrating the efficiency of the synthesis process. The study also highlights the environmental benefits of CPO biodiesel production, including reduced carbon emissions and sustainable cultivation practices. The study emphasizes the potential of CPO biodiesel as a sustainable energy solution, paving the way for a cleaner, more resilient future.